相対判断および絶対判断による負の時間順序効果の検討 - 濱田, 治良 (The Japanese Journal of Psychonomic Science, 1990)
The negative time order effect (TOE) was investigated in a weight-lifting experiment. After two stimuli were presented in succession, subjects judged the weights of the stimuli by means of the methods of relative and absolute judgments. As a control experiment, the weights of single stimuli were also judged. The results may be summarized as follows. (1) Amount of negative TOE measured by the absolute judgment was consistent with that obtained bythe relative one. (2) The result of the negative TOE obtained under the absolute judgment was that the first and the second stimuli were respectively lighter and heavier than the single stimulus. Sinking-trace theory and adaptation-level theory could not explain the results. In order to explain the negative TOE, we introduced the concept of "disinhibition". The concept explained the negative TOE as follows. When the first stimulus was raised, excitation and inhibition were induced. The weight sensation corresponded to the peak of the excitation. After the stimulus was lowered, the inhibition gradually reduced the weight sensation of the first stimulus in the course of time. Lifting the second stimulus caused disinhibition of neural activity with respect to the first stimulus. Next a summation between the excitation resulted from the disinhibition and the excitation for the second stimulus occurred. Thus, the first stimulus was judged lighter, and the second one heavier than the single stimulus.